2022
DOI: 10.1093/cercor/bhac008
|View full text |Cite
|
Sign up to set email alerts
|

Trauma moderates the development of the oscillatory dynamics serving working memory in a sex-specific manner

Abstract: Working memory, the ability to hold items in memory stores for further manipulation, is a higher order cognitive process that supports many aspects of daily life. Childhood trauma has been associated with altered cognitive development including particular deficits in verbal working memory (VWM), but the neural underpinnings remain poorly understood. Magnetoencephalography (MEG) studies of VWM have reliably shown decreased alpha activity in left-lateralized language regions during encoding, and increased alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…First, our behavioral findings indicated that older youth performed significantly faster and more accurately than younger youth, which has been reported by previous studies of verbal working memory in developing youth ( Embury et al, 2019 , Killanin et al, 2022 ). It is well known that developmental improvements in working memory are non-linear, with rapid gains occurring between late childhood and early adolescence ( Blakemore and Choudhury, 2006 , Diamond, 2013 , Theodoraki et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…First, our behavioral findings indicated that older youth performed significantly faster and more accurately than younger youth, which has been reported by previous studies of verbal working memory in developing youth ( Embury et al, 2019 , Killanin et al, 2022 ). It is well known that developmental improvements in working memory are non-linear, with rapid gains occurring between late childhood and early adolescence ( Blakemore and Choudhury, 2006 , Diamond, 2013 , Theodoraki et al, 2020 ).…”
Section: Discussionsupporting
confidence: 86%
“…Although MEG working memory studies have been conducted in child and adolescent samples ( Embury et al, 2019 , Heinrichs-Graham et al, 2021 , Heinrichs-Graham et al, 2022 , Killanin et al, 2022 ), only one has probed age-related changes in a typically developing sample ( Embury et al, 2019 ). In the current investigation, we examined a younger (6–14 years-old), and larger, sample of typically developing youths and focused on the neural oscillatory activity that supports the encoding and maintenance phases of verbal working memory.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous work has found alpha, beta, and gamma each to be important in mediating perception and attention, particularly in the parietal cortex ( Misselhorn et al, 2019 , Zaretskaya and Bartels, 2015 ). Specifically, during this developmental period, increases in theta activity have been reported during abstract reasoning ( Taylor et al, 2020 ) and selective attention performance ( Taylor et al, 2021 ), age-related changes in visual gamma activity have been seen during basic visual processing ( Fung et al, 2021 ), alterations in alpha activity have been reported during verbal working memory processing ( Embury et al, 2019 , Killanin et al, 2022 ), and beta and gamma oscillations have been found to change in relation to a developing sensorimotor system ( Heinrichs-Graham et al, 2018 , Trevarrow et al, 2019 , Wilson et al, 2010 ). In the current study, beta and gamma activity increased with increasing DHEA in posterior parietal and occipital regions of the brain, which are in line with roles in attention and early sensory processing.…”
Section: Discussionmentioning
confidence: 98%
“…However, gender differences in the functional dynamics supporting cognition are understudied. Preliminary evidence from task-based MEG studies in children and adolescents indicates potential sex-specific developmental effects during various cognitive tasks (Embury et al, 2019 ; Killanin et al, 2020 , 2022 ; Taylor et al, 2020 ; Fung et al, 2021 ). MEG studies in adults have also shown gender differences neural responses during spatial navigation (Pu et al, 2020 ), face processing (Proverbio, 2021 ), and resting-state networks throughout the lifespan (Rempe et al, 2023 ; Stier et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%